Mining the red sea metagenomics libraries for betaine pathways - Allam, Sherouk (AUC Knowledge Fountain, 2018)
Glycine Betaine (GB) is a fundamental solute for salinity tolerance in many organisms. Our aim in this study was to identify the GB pathway in highly complex natural community inhabiting brine pool and Red Sea column in Atlantis II Red Sea. Environmental genomics is a powerful tool for collecting information on microbial communities. Knowledge can be collected about highly complex natural communities. Microbial community living in extreme conditions evolved divers molecular mechanisms to withstand these conditions. Metagenomic libraries from Atlantic II samples were used to study betaine biosynthetic pathway that is more abundant. Betaine is synthesized independently from two different substrates, Choline and Glycine, through two oxidation and three methylation enzymatic steps, respectively. A comparative sequence based analysis was made for the enzymes of the two branches in GB pathway. Assembled sequences were blasted, and comparisons were done on number of occurrence. Some more procedures were accomplished, to ensure that data encountered are valid, and to eliminate false hits. Conserved domain was checked in blast results. The existence of the active sites indicates enzymes activity. Species were mapped to ensure that the enzymes in each pathway exited in the same species. After conducting analysis, it was found that Choline Pathway enzymes were encountered in abundance in targeted sites. The conserved domains of the enzymes, CDH and BADH, were found in vast amounts as well. In a comparative analysis between Choline pathway and Glycine pathway, data was normalized to show number of hits with consideration to sample size. It is found that in Salinity 4% in depth 200m, Choline Pathway recorded 0.0115, and Glycine pathway had 0.029. Whereas, in Salinity 4% in depth V 700m, Choline Pathway had 0.53 hits, and Glycine Pathway had a record of 0.02. Salinity 8% in depth 1500m, Choline Pathway had 1.6, and Glycine Pathway had 0.46. In Salinity 9-16% in UCL, Choline Pathway was 1.2 and Glycine Pathway had 0.11 records. In Salinity 26% in LCL, Choline Pathway was recorded into 1.02, where as, Glycine Pathway had 0.13 records. The records indicates that adaptation encountered by Choline pathway tends to be preferable pathway for the targeted community. Glycine pathway, on the other hand, was found in less abundance. The environment in most depths showed less bias to Glycine PW, but had consistent increase with the increase of salinity, the more salinity the more the enzymes were available in full length. Glycine pathway enzymes and their active domains that appeared through depths in accordance with salinity could be more conserved and that is the reason for their conservative abundance.